2011
DOI: 10.1177/0306624x10396441
|View full text |Cite
|
Sign up to set email alerts
|

Moral Development and Recidivism: A Meta-Analysis

Abstract: A meta-analysis of 19 studies (N = 15,992 offenders) showed a significant inverse relation between more mature moral development and recidivism. Moderator analyses revealed a larger effect size for moral cognition (r = .20) than for moral emotion (r = .11). Effect sizes for production measures (r = .57) were much larger than for recognition measures (r = .16) and unstructured (clinical) judgment (r = .10). Larger effect sizes were found for female delinquents (r = .32) than for male delinquents (r = .21).Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Self-conscious emotions are less researched in relation to delinquency than other aspects of moral development, such as the cognitive component of morality and empathy (Stams et al, 2006;Van Langen, Wissink, Van Vugt, Van der Stouwe, & Stams, 2014;Van Vugt et al, 2011). When the strength of the relation between self-conscious emotions and delinquency found in the current study is compared with the findings of meta-analyses on the relation between moral judgement and empathy, it shows the importance of self-conscious emotions, and especially guilt, as part of the role of moral development in delinquent behavior.…”
Section: Self-conscious Emotions and Delinquencymentioning
confidence: 99%
“…Self-conscious emotions are less researched in relation to delinquency than other aspects of moral development, such as the cognitive component of morality and empathy (Stams et al, 2006;Van Langen, Wissink, Van Vugt, Van der Stouwe, & Stams, 2014;Van Vugt et al, 2011). When the strength of the relation between self-conscious emotions and delinquency found in the current study is compared with the findings of meta-analyses on the relation between moral judgement and empathy, it shows the importance of self-conscious emotions, and especially guilt, as part of the role of moral development in delinquent behavior.…”
Section: Self-conscious Emotions and Delinquencymentioning
confidence: 99%
“…The appropriateness of such a strategy is supported by a recent meta-analysis that found a negative relationship between moral development and the recidivism of offenders. A total of 19 correlations generated an overall effect size with offender recidivism of r = .11, with moral cognition producing a stronger effect, r = .20, than moral emotion, r = .11 (Van Vugt et al, 2011). In their metaanalysis of 50 studies comparing juvenile delinquents to nondelinquents, Stams et al (2006) found that delinquency was strongly associated with developmentally delayed moral judgment, even when controlling for issues such as age, gender, socioeconomic status, and intelligence.…”
Section: A Theoretical Basis For Mrtmentioning
confidence: 99%
“…Criminal offenders have lower scores on moral reasoning tests than do non-offenders (Stams et al 2006), a group difference that is likely mediated by deficits in cognitive empathy and general intelligence (O'Kane et al 1996;Van Langen et al 2014). Among criminal offenders, lower moral reasoning scores predict increased recidivism (Van Vugt et al 2011) and psychopathic traits predict deficits in detecting social contract violations (Ermer & Kiehl 2010). Both lines of evidence suggest that recalcitrant offenders have difficulty obtaining and applying moral knowledge.…”
Section: Introductionmentioning
confidence: 99%